PANJANG RAMBUT NABI MUHAMMAD SAW. (Studi Ma‘ani al-Hadis dan Implementasinya pada Jamaah an-Nadzir Gowa – Sulawesi Selatan) - Munadi, Radhie (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2020)
The many schools in Islam in Indonesia make a diversity of understanding of the hadith. The diversity of understanding can be seen from their practice in accordance with their respective understanding. Among them is the understanding of Jamaah an-Nadzir in practicing the sunnah of the Prophet's hair by lengthening his hair to the shoulder. These differences encourage researchers to conduct research on the hadith nature of the Prophet's hair. This article tries to examine how the concept of the Prophet's hair is accommodated by the hadith, and how the implementation of the hadith in the Jamaah an-Nadzir. Research is expected to provide a comprehensive understanding of the concept of the Prophet's hair in line with the hadith.